Symmetry and Liquid Crystals - Ishihara, Shoichi; Uto, Sadahito (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Currently, the global liquid crystal (LC) industry is worth approximately USD 115 billion, most of which is used for display applications using nematic LCs (including chiral nematic LCs). The purpose of this Special Issue is to provide new knowledge and research tools as the application of LC devices expands from flat displays to new fields such as 3D displays and sensors. This issue will provide LC researchers with ways to solve their problems.